EVALUASI IMPLEMENTASI KURIKULUM ROBOTIKA PADA SMPIT INSAN SEJAHTERA SUMEDANG - Riffandi, Destryana; Rusman, Rusman (STKIP PGRI Situbondo, 2024)
The purpose of this study is to describe the evaluation of the implementation of the robotics curriculum. Research place at SMPIT Insan Sejahtera Sumedang. Evaluation of the implementation of the robotics curriculum in research using a descriptive evaluation method of case study design with a qualitative approach. The evaluation model used in this study adopts the CIPP evaluation model which is limited to input, process, and product components. Participants in this study were principals, vice principals, robotics teachers and students of SMPIT Insan Sejahtera class IX. The criteria in this study also act as an instrument in conducting evaluation research. The data collection technique used in this study was a semi-structured interview. The results showed that in general, the evaluation of the implementation of the robotics curriculum at SMPIT Insan Sejahtera has shown good results even though there are several aspects that still require attention and improvement for the success of learning implementation in the future. Some aspects that need to be considered come from input components such as teacher competence, learning infrastructure, and supervision of the fulfillment of learning outcomes. While the process component is related to a series of learning planning, one of which is the selection of learning methods that are considered inappropriate to be applied to students. All aspects of the curriculum product component show good results and are in accordance with research evaluation criteria.